Knowledge about Anemia and Physical Activity with the Incidence of Anemia Among Adolescent Girls - Haniyyah Prastia Putri; A'immatul Fauziyah (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Adolescent girls with anemia in Indonesia was still high. Adolescents, especially girls were prone to anemia due to their menstrual cycle every month. This cross-sectional study intended to analyze the relationship between knowledge about anemia and physical activity of adolescent girls with the anemia incidence. This research was conducted in MTs. Fadlurrahman, Bekasi, West Java, Indonesia in 2022. This cross-sectional study with 49 samples used stratified random sampling to determine the subjects. The result showed that 36,7% of subjects had anemia, 69,4% had low knowledge and 65,31% had low activity. Chi-square analysis indicated that knowledge of anemia in adolescent girls significantly (p<0,05) related to anemia incidence, but no significant (p>0,05) relationship between physical activity in adolescent girls with the anemia incidence. These findings indicated that increasing the knowledge was important to prevent anemia. Physical activity did not directly affect anemia incidence and needs further investigation.